Work-Life Balance, Work Environment, dan Job Satisfaction: Studi Fenomenologi pada Dosen Tetap Universitas Swasta - Lina Parlina (Program Studi Administrasi Bisnis, 2026)
Lecturers at private universities face growing pressure to balance higher education duties with personal life, while navigating physical and social work conditions that shape their job satisfaction. This study describes how permanent lecturers at a private university experience Work-Life Balance, perceive their Work Environment, and make sense of their Job Satisfaction, and how these three foci are interrelated. A qualitative phenomenological design was used, involving 59 permanent lecturers selected through purposive sampling until data saturation. Data were collected through open-ended questionnaires and documentation review, analyzed using the Miles and Huberman interactive model of data reduction, display, and conclusion drawing, with credibility established through source triangulation and member checking. Findings show most informants experienced time-related strain from work into personal life, yet remained satisfied with their overall balance through adaptive strategies such as scheduling and boundary-setting. The non-physical work environment, particularly collaborative culture and supportive relationships, mattered more to informants' comfort than physical facilities. Job satisfaction was driven mainly by intrinsic aspects of teaching and research, while administrative workload and compensation gaps were the main sources of dissatisfaction. The three foci were reciprocally related, suggesting that integrated institutional policies on flexibility, workplace culture, facilities, and compensation are needed to sustain lecturers' job satisfaction